Isolasi dan Karakterisasi Fungi Endofit dari Daun Tanaman Bintaro (Cerbera odollam) yang Berpotensi sebagai Antibakteri - Wonowijaya, Suwandi; Soegianto, Lisa (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
The need of antibiotics is increasing, spurred to find compounds that have antimicrobial activity from natural ingredients. One way to obtain antimicrobial compounds is through endophytic fungi. This study aimed to isolate and characterize endophytic fungi obtained from the leaves of the plant Bintaro (Cerbera odollam) that potential as an antibacterial against Staphylococcus aureus and Escherichia coli. Leaf surface was sterilized by soaking in 70% alcohol for 2 minutes, 5.3% sodium hypochlorite for 5 minutes, 70% alcohol for 1 minute, rinsed with sterile distilled water and dried using sterile wipes. Bintaro leaf that have been sterilized was puton Potato Dextrose Agar (PDA) and then incubated at room temperature for 7-14 days. The growing fungi was inoculated in Potato Dextrose Yeast (PDY) for 7-14 days at room temperature based on the macroscopic difference. Endophytic fungi that have been purein macroscopic way was tested antibacterial activity on Staphylococcus aureus and Escherichia coli and continued to macroscopic and microscopic observation. Obtained three types of endophytic fungi were isolated from bintaro leaves (Cerbera odollam) with the code EB 1, EB 2 and EB 3 that suspected from genus Fusarium, Geotrichum and Aspergillus. The antibacterial activity test show that results of three endophytic fungi obtained has no antibacterial activity against Staphylococcus aureus and Escherichia coli.